A Conserved Aspartate Determines Pore Properties of Anion Channels Associated with Excitatory Amino Acid Transporter 4 (EAAT4) - Kovermann, Peter (American Society for Biochemistry and Molecular Biology, 2010)
Excitatory amino acid transporter (EAAT) glutamate transporters function not only as secondary active glutamate transporters but also as anion channels. Recently, a conserved aspartic acid (Asp(112)) within the intracellular loop near to the end of transmembrane domain 2 was proposed as a major determinant of substrate-dependent gating of the anion channel associated with the glial glutamate transporter EAAT1. We studied the corresponding mutation (D117A) in another EAAT isoform, EAAT4, using heterologous expression in mammalian cells, whole cell patch clamp, and noise analysis. In EAAT4, D117A modifies unitary conductances, relative anion permeabilities, as well as gating of associated anion channels. EAAT4 anion channel gating is characterized by two voltage-dependent gating processes with inverse voltage dependence. In wild type EAAT4, external l-glutamate modifies the voltage dependence as well as the minimum open probabilities of both gates, resulting in concentration-dependent changes of the number of open channels. Not only transport substrates but also anions affect wild type EAAT4 channel gating. External anions increase the open probability and slow down relaxation constants of one gating process that is activated by depolarization. D117A abolishes the anion and glutamate dependence of EAAT4 anion currents and shifts the voltage dependence of EAAT4 anion channel activation by more than 200 mV to more positive potentials. D117A is the first reported mutation that changes the unitary conductance of an EAAT anion channel. The finding that mutating a pore-forming residue modifies gating illustrates the close linkage between pore conformation and voltage- and substrate-dependent gating in EAAT4 anion channels.